Identifikasi Risiko Kecelakaan Kerja Pada Proyek Pembangunan Passenger Terminal Building Bandara Internasional Dhoho Kediri - Putri, Intan Ersalina Hazlinda (Jurnal Vokasi Teknik Sipil, 2023)
The Passenger Terminal Building for the Dhoho Kediri International Airport Project is a fairly complex building, so it is necessary to study the types of work accident risks that may occur during the construction process at the building structure work stage. This research was using the literature review methode and discussion or direct interviews with the K3/SHE Unit which aims to identifying risks that might occur during the construction process of the Dhoho Kediri International Airport Passenger Terminal Building, identifying risks in. Based on the output results from the risk identification stage, 46 work accident risk variables were obtained, with 39 risks obtained through literature study and 7 risks obtained through discussions or direct interviews with the K3/SHE Unit. In the risk validation stage of the 46 identified risk variables, there are 2 (two) risk variables that are considered irrelevant, namely the risk of tool failure when using heavy equipment during land clearing for preparatory work and excavation-backfill work, and there is an addition of 1 (one) the new risk variable from the respondents is the risk of electric shock in the use of concrete vibrators in foundry work, so that the number of risk variables becomes 45 variables.